2019
DOI: 10.1093/toxsci/kfz233
|View full text |Cite
|
Sign up to set email alerts
|

High-Content Image-Based Single-Cell Phenotypic Analysis for the Testicular Toxicity Prediction Induced by Bisphenol A and Its Analogs Bisphenol S, Bisphenol AF, and Tetrabromobisphenol A in a Three-Dimensional Testicular Cell Co-culture Model

Abstract: Emerging data indicate that structural analogs of bisphenol A (BPA) such as bisphenol S (BPS), tetrabromobisphenol A (TBBPA), and bisphenol AF (BPAF) have been introduced into the market as substitutes for BPA. Our previous study compared in vitro testicular toxicity using murine C18-4 spermatogonial cells and found that BPAF and TBBPA exhibited higher spermatogonial toxicities as compared with BPA and BPS. Recently, we developed a novel in vitro three-dimensional (3D) testicular cell co-culture model, enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…An intriguing observation was the higher proportion of cells showing signs of DNA damage ( Figure 1F–H ). Previous data from a testicular coculture model indicated that BPA had no effect on the proportion of cells with signs of DNA damage when cultured for up to 72 h and at BPA concentrations up to ( Yin et al. 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An intriguing observation was the higher proportion of cells showing signs of DNA damage ( Figure 1F–H ). Previous data from a testicular coculture model indicated that BPA had no effect on the proportion of cells with signs of DNA damage when cultured for up to 72 h and at BPA concentrations up to ( Yin et al. 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…2016 ; Sahu et al. 2020 ; Yin et al. 2020 ), we also examined the proportion of cells staining positive for , a marker of DNA damage ( Rogakou et al.…”
Section: Resultsmentioning
confidence: 99%
“…Image-based profiling identified rosmarinic acid as a candidate with cardioprotective effects against the toxicity of doxorubicin 91 . This approach also revealed the toxic effects of bisphenol A and its analogues on a testicular cell co-culture model by simultaneously measuring multiple adverse end points such as changes to nuclear morphology and cytoskeletal structure 92 .…”
Section: Lead Generationmentioning
confidence: 99%
“…Yin et al. ( 24 ) determined an early DNA damage response marker γ-H2AX to assess the genotoxicity of TBBPA in mouse testicular cell co-culture model. They observed that after 24 h of incubation, TBBPA at 15 µM (8.1 µg/mL) caused significant increase of the number of γ-H2AX positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, earlier studies have shown no genotoxic effects of TBBPA that could have been associated with the use of very low doses of this compound ( 19 – 21 ). However, more recent studies have indicated genotoxic potential of TBBPA in spermatozoa of mice ( 22 ), blood cells of spotted snake ( Channa punctatus ) ( 23 ) and mouse testicular cell co-culture model ( 24 ). 2,4,6-TBP was not genotoxic in in vitro bacterial tests ( 25 , 26 ); however, it caused chromosomal aberrations (with and without metabolic activation) in in vitro tests on Chinese hamster cells ( 27 ).…”
Section: Introductionmentioning
confidence: 99%